Historias de esta vieja Facultad de Filosofía y Letras - García Guatas, Manuel (Artigrama, 2006)
Cercanas las obras de remodelación de la Facultad de Filosofía y Letras, hemos querido incluir este breve estudio sobre la decoración mural realizada en 1959 en el primitivo bar-comedor de esta Facultad por su curiosidad artística, historia del edificio y recuerdo de su autor, un alumno entonces, ahora catedrático de Literatura y académico de la Lengua. Now, as the remodelling work at the Faculty of Arts approaches, we would like to include this brief study about the mural decoration made in 1959 in the first and original bar-dining hall of this faculty because of its artistic curiosity, the interesting history of the building and remembering the artist, a student at that time, today professor of Literature and member of the Academy of Spanish Language.